Application of Neuroscience in Education - Ahmad Taufik Hidayat; Abdul Quddus (Universitas Muhammadiyah Enrekang, 2023)
Neuroscience is a part of biology that focuses on systems and nerve cells in the brain. The science of nerve cells and brain work systems has an interesting focal point, which is to find out how the human brain works in every activity and action performed. In the learning process, the application of neuroscience can be said to be appropriate to help the learning process become more optimal by maximizing brain work. That is one of the goals of neuroscience, which is to be able to maximize the work of the learner's brain in the learning process and to make learning more meaningful and more interesting for the students themselves. But, of course, the application of neuroscience cannot be done directly in the classroom. It must go through several connecting aspects first, such as neuroscience, cognitive neuroscience, psychological mechanisms, educational theory and then the classroom. In other words, the application of neuroscience in the teaching process still takes time, considering some of the aspects mentioned earlier.